Efficient narrow-band blue fluorescent material as well as preparation method and application thereof

By creating gap atomic defects in fluorescent materials and using high-temperature solid phase reactions, an efficient narrowband blue fluorescent material was prepared, which solved the problem of unidirectional and defective luminescence performance in the prior art resulting in the degradation of luminescence performance, and achieved the effect of efficient, narrowband and blue light emission.

CN119685016AActive Publication Date: 2025-03-25XIAMEN UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411871297.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-25
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The emission spectral regulation direction of existing fluorescent materials is unidirectional, and the presence of defects leads to a degradation of luminescence performance, making it difficult to prepare highly efficient narrowband blue fluorescent materials.

Method used

By creating gap atomic defects in a fluorescent material with the chemical formula Ba2-xEuxHf2+ySi5-4yAl2+4yO19, a high-efficiency narrowband blue fluorescent material was prepared by using high-temperature solid phase reaction.

Benefits of technology

Under 400 nm purple light excitation, the main peak of the emission spectrum is located at 455-475 nm, the half-height width is in the range of 70-80 nm, the quantum efficiency is >70%, and the crystal structure of the material belongs to a hexagonal crystal system, with a space group of P63/m.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685016A_ABST
    Figure CN119685016A_ABST
Patent Text Reader

Abstract

The invention discloses an efficient narrow-band blue fluorescent material as well as a preparation method and application thereof, and relates to the field of fluorescent materials. The chemical formula of the fluorescent material is Ba (2-x) EuxHf (2 + y) Si (5-4y) Al (2 + 4y) O19, x is more than 0 and less than or equal to 0.05, and y is more than or equal to 0.1 and less than or equal to 0.5. The crystal structure of a matrix corresponding to the material belongs to a hexagonal system, and the space group is P63 / m. According to the fluorescent material, Eu < 2 + > serves as an activating agent, under excitation of 400 nm purple light, the main peak of an emission spectrum is located at 455-475 nm, the full width at half maximum is 70-80 nm, and the quantum efficiency is larger than 70%, so that the fluorescent material can be applied to white light LED devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of fluorescent materials, and in particular to a high-efficiency narrow-band blue fluorescent material and a preparation method and application thereof. Background Art

[0002] As the most common lighting product currently, white LED light sources have entered thousands of households. The most common way for white LED light sources to output white light, as disclosed in Patent Document 1 (Yu Binhai, Li Xufeng, Li Cheng, Chen Canwei, White Light Emitting Diode Phosphor Coating Liquid and Preparation Method and Coating Method thereof, CN102002269B), is to use the light emitted by the LED chip to excite the fluorescent material, and the light emitted by the fluorescent material under excitation and the light (emitted by the LED) that is not (completely) absorbed by the fluorescent material are mixed with each other to finally obtain white light. Obviously, fluorescent materials are the key to making white LED light sources.

[0003] As a functional material, the performance parameters of fluorescent materials include emission spectrum characteristics, luminous intensity, quantum efficiency, etc. In particular, the emission spectrum, the position of its main peak has a great influence on the light, color and electrical quality of white light LEDs, so it is particularly important to regulate the emission spectrum of fluorescent materials. Common emission spectrum control methods, such as those disclosed in Patent Document 2 (Mao Zhiyong, Chen Jingjing, Wang Dajian, Lu Zhijuan, Xu Jiao, Yang Yanfang, a multicolor fluorescent material with crystal form control, preparation method and application thereof, CN105238396A), can control the emission spectrum of the fluorescent material by changing the crystal form; as disclosed in Patent Document 3 (Wu Zhanchao, Huang Chong, Liu Jie, a new type of spectrally adjustable self-activated phosphor, CN108251112B), the emission spectrum is controlled by adjusting the crystal field; as disclosed in Patent Document 4 (Pan Zaifa, Wang Lili, Liu Shuang, Mo Weimin, a single-matrix white light phosphor for white light LEDs and preparation method thereof, CN102559179A), the spectrum is controlled by adjusting the ratio of different luminescence centers and relying on energy transfer between luminescence centers.

[0004] Generally, the direction of spectrum regulation is unidirectional. That is, by changing the regulation parameters, the emission spectrum of the fluorescent material will move in a specific direction (for example, the long wavelength direction, such as red light; or the short wavelength direction, such as blue light). For example, Patent Document 5 (Ye Qiaowen, Liu Ruxi, Adjustable Phosphor for Luminescence, CN102734752B) discloses a spectrum-adjustable nitride fluorescent material, whose chemical formula is (AE)Si 6-p Al pN8, wherein AE is an alkaline earth metal and a doped rare earth element RE, p is a parameter defining the relative aluminum content by weight and p is greater than zero. As the p value increases, the main peak of the emission spectrum of the fluorescent material can be adjusted from the blue light region (452 ​​nm) to the red light region (604 nm); as in patent document 6 (Liu Ronghui, Qin Shaowei, Liu Yuanhong, Li Yanfeng, Chen Xiaoxia, Ma Xiaole, Xue Yuan, a garnet structure phosphor and a light-emitting device containing the phosphor, CN113416544B) discloses a spectrally adjustable garnet structure fluorescent material, the fluorescent material comprising 38.47% to 45.19% of Y element, 9.49% to 22.09% of Al element, 2.06% to 24.31% of Ga element, 27.3% to 32.04% of O element, and 0.43% to 1.46% of Ce element by weight. With the increase of Ga content, the main peak of the emission spectrum of the fluorescent material can be adjusted from 531 nm to 517 nm.

[0005] Defects are common in materials. For fluorescent materials, common defects are point defects, including vacancies and interstitial atoms. For fluorescent materials, as disclosed in non-patent document 1 (Xin Pan, Lefu Mei, Yixi Zhuang, Takatoshi Seto, Yuhua Wang, Mikhail Plyaskin, Wei Xi, Chao Li, Qingfeng Guo, Libing Liao, Anti-Defect engineering toward high luminescent efficiency in whitlockite phosphors), the presence of defects will significantly reduce the luminescent properties (such as quantum efficiency) of fluorescent materials, so defects should be avoided as much as possible in the process of synthesizing fluorescent materials.

[0006] In summary, it is generally believed that the emission spectrum of fluorescent materials can be unidirectionally adjusted, and defects in fluorescent materials should be avoided as much as possible. 2-x Eu x Hf 2+y Si 5-4y Al 2+4y O 19 By manufacturing defects in the fluorescent material (where 0<x≤0.05, 0.1≤y≤0.5), a high-efficiency narrow-band blue fluorescent material that can be excited by violet light is finally obtained. Under the excitation of 400 nm violet light, the main peak of the emission spectrum is located at 455-475 nm, the half-width of the emission spectrum is in the range of 70-80 nm, and the quantum efficiency is greater than 70%. The corresponding matrix of the fluorescent material (BaHf2Si5Al2O 19) belongs to the hexagonal crystal system, and the space group is P63 / m. The high efficiency, narrow band, blue light emission behavior of the fluorescent material is disclosed for the first time in the present invention. Summary of the invention

[0007] The purpose of the present invention is to solve the above problems in the prior art and provide a high-efficiency narrow-band blue fluorescent material and its preparation method and application. Under the excitation of 400 nm purple light, the main peak of the emission spectrum of the high-efficiency narrow-band blue fluorescent material is located at 455-475 nm, the half-width of the emission spectrum is 70-80 nm, and the quantum efficiency is greater than 70%.

[0008] Therefore, a first object of the present invention is to provide a high-efficiency narrow-band blue fluorescent material.

[0009] A highly efficient narrow-band blue fluorescent material, which can be represented by the following chemical formula:

[0010] Ba 2-x Eu x Hf 2+y Si 5-4y Al 2+4y O 19

[0011] Among them, 0<x≤0.05, 0.1≤y≤0.5.

[0012] Preferably, x may be 0.03, and y may be 0.3.

[0013] The second object of the present invention is to provide a method for preparing a high-efficiency narrow-band blue fluorescent material. The preparation method comprises the following steps: mixing a Ba precursor, a Eu precursor, a Hf precursor, a Si precursor and an Al precursor, and performing a high-temperature solid-phase reaction under a reducing atmosphere to obtain a high-efficiency narrow-band blue fluorescent material.

[0014] Preferably, the molar ratio of Ba, Eu, Hf, Si and Al in the Ba precursor, Eu precursor, Hf precursor, Si precursor and Al precursor is (2-x):x: (2+y):(5-4y):(2+4y), wherein 0<x≤0.05, 0.1≤y≤0.5.

[0015] Preferably, the Ba precursor is selected from one or more of Ba carbonate, Ba oxide, Ba oxalate and Ba nitrate; the Eu precursor is selected from one or more of Eu carbonate, Eu oxide, Eu oxalate and Eu nitrate; the Hf precursor is selected from HfO2; the Si precursor is selected from SiO2; the Al precursor is selected from one or more of Al carbonate, Al oxide, Al oxalate and Al nitrate.

[0016] Preferably, the purity of the Ba precursor, Eu precursor, Hf precursor, Si precursor and Al precursor is not less than 99.5%.

[0017] Preferably, the temperature of the high-temperature solid-phase reaction is 1400-1600° C., the atmosphere is a reducing atmosphere, and the time of the high-temperature solid-phase reaction is 4-10 hours.

[0018] Another object of the present invention is to provide a white light LED device. The white light LED device comprises a high-efficiency narrow-band blue fluorescent material (whose chemical formula is: Ba 2-x Eu x Hf 2+y Si 5-4y Al 2+4y O 19 , where 0<x≤0.05, 0.1≤y≤0.5) and the main peak of the emission spectrum is located between 380 and 425 nm.

[0019] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0020] The present invention intentionally creates (interstitial atom) defects in the fluorescent material, which unexpectedly causes the main peak position of the fluorescent material emission spectrum to change, and at the same time, the quantum efficiency of the fluorescent material is significantly enhanced. Finally, the present invention provides a high-efficiency narrow-band blue fluorescent material with a new crystal structure. The chemical formula of the fluorescent material is: Ba 2-x Eu x Hf 2+ y Si 5-4y Al 2+4y O 19 , where 0<x≤0.05, 0.1≤y≤0.5. The matrix corresponding to the fluorescent material (Ba2Hf2Si5Al2O 19 ) belongs to the hexagonal crystal system, and the space group is P63 / m. 2+ It is the luminescence center, with the strongest excitation peak located near 400 nm, the main peak of the emission spectrum located at 455-475 nm, the half-width at half maximum in the range of 70-80 nm, and the quantum efficiency >70%, so that the fluorescent material can be used in the packaging of white light LED devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is the emission spectrum of the material obtained in Comparative Example 1 under 400 nm excitation.

[0022] Figure 2 It is the emission spectrum of the material obtained in Comparative Example 4 under 400 nm excitation.

[0023] Figure 3 The excitation and emission spectra of the material obtained in Example 1 are shown in FIG.

[0024] Figure 4 The X-ray diffraction pattern of the material obtained in Example 1 is shown in FIG.

[0025] Figure 5 : is the crystal structure diagram of the material (corresponding matrix) obtained in Example 1.

[0026] Figure 6 The graph is a graph showing changes in the luminescence properties of the materials obtained in Examples 1 to 5.

[0027] Figure 7 The graphs are of the changes in the luminescence properties of the materials obtained in Examples 6 to 10.

[0028] Figure 8 The graph is a graph showing changes in the luminescence properties of the materials obtained in Examples 11 to 15.

[0029] Fig. 9 This is a graph showing changes in the luminescence properties of the materials obtained in Examples 16 to 20.

[0030] Fig.10 This is a graph showing changes in the luminescence properties of the materials obtained in Examples 21 to 25.

[0031] Fig.11 This is a graph showing changes in the luminescence properties of the materials obtained in Examples 26 to 30.

[0032] Fig.12 This is the spectrum of the white light LED device obtained in Example 31. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0034] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0035] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present invention can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0036] The present invention provides a high-efficiency narrow-band blue fluorescent material, which can be expressed by the following chemical formula:

[0037] Ba 2-x Eu x Hf 2+y Si 5-4y Al2+4y O 19 ,

[0038] Among them, 0<x≤0.05, 0.1≤y≤0.5.

[0039] In Examples 1 to 5 of the present invention, x is preferably 0.005, and y is preferably 0.1, 0.2, 0.3, 0.4, and 0.5; in Examples 6 to 10 of the present invention, x is preferably 0.01, and y is preferably 0.1, 0.2, 0.3, 0.4, and 0.5; in Examples 11 to 15 of the present invention, x is preferably 0.02, and y is preferably 0.1, 0.2, 0.3, 0.4, and 0.5; in Examples 16 to 20 of the present invention, x is preferably 0.03, and y is preferably 0.1, 0.2, 0.3, 0.4, and 0.5; in Examples 21 to 25 of the present invention, x is preferably 0.04, and y is preferably 0.1, 0.2, 0.3, 0.4, and 0.5; in Examples 26 to 30 of the present invention, x is preferably 0.05, and y is preferably 0.1, 0.2, 0.3, 0.4, and 0.5.

[0040] The present invention also provides a method for preparing a high-efficiency narrow-band blue fluorescent material, the steps of which are as follows: mixing a Ba precursor, a Eu precursor, a Hf precursor, a Si precursor and an Al precursor, and performing a high-temperature solid-phase reaction under a reducing atmosphere to obtain a high-efficiency narrow-band blue fluorescent material.

[0041] In the above steps, the molar ratio of Ba, Eu, Hf, Si and Al in the Ba precursor, Eu precursor, Hf precursor, Si precursor and Al precursor is (2-x):x:(2+y):(5-4y):(2+4y), wherein 0<x≤0.05, 0.1≤y≤0.5.

[0042] In the above steps, the Ba precursor can be a compound containing Ba well known in the art, without any special restrictions. In the present invention, it is preferably one or more of Ba carbonate, Ba oxide, Ba oxalate and Ba nitrate, and more preferably Ba carbonate, i.e. BaCO3; the Eu precursor can be selected from one or more of Eu carbonate, Eu oxide, Eu oxalate and Eu nitrate, and more preferably Eu oxide, i.e. Eu2O3; the Hf precursor is selected from HfO2; the Si precursor is selected from SiO2; the Al precursor can be a compound containing Al well known in the art, without any special restrictions. In the present invention, it is preferably one or more of Al carbonate, Al oxide, Al oxalate and Al nitrate, and more preferably Al oxide, i.e. Al2O3.

[0043] The purity of the above-mentioned Ba precursor, Eu precursor, Hf precursor, Si precursor and Al precursor is not less than 99.5%. The higher the purity, the less impurities in the obtained phosphor.

[0044] In the above steps, the temperature of the high-temperature solid phase is preferably 1400-1600°C, and the atmosphere is a reducing atmosphere; in some embodiments provided by the present invention, the temperature of the high-temperature solid phase is preferably 1500°C; the reducing atmosphere can be a reducing atmosphere well known to those skilled in the art, and there is no special limitation. In the present invention, a nitrogen-hydrogen mixed atmosphere with a volume ratio of 9:1 is preferred.

[0045] The high temperature solid phase time in the above steps is preferably 4 to 10 hours, more preferably 5 to 8 hours; in some embodiments provided by the present invention, the high temperature solid phase time is preferably 6 hours.

[0046] The high temperature solid phase reaction is preferably carried out in a high temperature furnace; after the reaction is carried out, the furnace is cooled to room temperature to obtain a high efficiency narrow band blue fluorescent material.

[0047] The embodiment of the present invention adopts a high temperature solid phase reaction to successfully prepare a high-efficiency narrow-band blue fluorescent material.

[0048] The present invention also provides a white light LED device. The white light LED device comprises at least Ba 2-x Eu x Hf 2+y Si 5-4y Al 2+ 4y O 19 , (where 0<x≤0.05, 0.1≤y≤0.5) chemical formula represents a high-efficiency narrow-band blue fluorescent material and a purple LED chip that can generate light within 380-425 nm. The specific production steps include: mixing a high-efficiency narrow-band blue fluorescent material with a green fluorescent material, a red fluorescent material and an epoxy resin, coating them on a purple LED chip with a main peak of emission wavelength at 380-425 nm, and then curing them at 150°C for 2h to obtain a white light LED device.

[0049] In order to further illustrate the present invention, a high-efficiency narrow-band blue fluorescent material and a preparation method thereof provided by the present invention are described in detail below in conjunction with embodiments.

[0050] The reagents used in the following comparative examples and embodiments are all commercially available.

[0051] Comparative Example 1

[0052] The raw materials are BaCO3, Eu2O3, HfO2, SiO2 and Al2O3. The molar ratio of Ba, Eu, Hf, Si and Al in BaCO3, Eu2O3, HfO2, SiO2 and Al2O3 is 1.97:0.03:2:5:2. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1500℃ for 6h in a high temperature furnace under a 9:1 nitrogen and hydrogen mixed atmosphere. Then, the theoretical chemical composition is Ba 1.97 Eu 0.03 Hf2Si5Al2O 19 materials.

[0053] The material obtained in Comparative Example 1 has no (significant) defects. This is because although Eu replaces Ba, the charge number is the same, the radius is close, and the amount of all elements is configured according to the stoichiometric ratio. Therefore, in theory, the material obtained in Comparative Example 1 should have a higher quantum efficiency. This is indeed the case. The luminescence performance of the corresponding material in Comparative Example 1 was analyzed using a fluorescence spectrometer, as shown in FIG. Figure 1 As shown. The results show that the main peak of the emission spectrum of the material obtained in Comparative Example 1 is located at 510 nm, which is cyan light, and the half-height width of the emission spectrum is 85 nm. The quantum efficiency of the material corresponding to Comparative Example 1 was tested using a quantum efficiency tester. The results show that the quantum efficiency of the material obtained in Comparative Example 1 is 77.3%, which is an extremely high value. Specific data are shown in Table 1. Due to the absence of defects, although the material obtained in Comparative Example 1 is not a blue luminescent material, its luminescent performance is excellent.

[0054] That is, Comparative Example 1 is a cyan-green light-emitting material with excellent performance.

[0055] Comparative Example 2

[0056] The raw materials are BaCO3, Eu2O3, HfO2, SiO2 and Al2O3. The molar ratio of Ba, Eu, Hf, Si and Al in BaCO3, Eu2O3, HfO2, SiO2 and Al2O3 is 1.97:0.03:2.6:2.6:4.4. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1500℃ for 6h in a high temperature furnace under a 9:1 nitrogen and hydrogen mixed atmosphere. Then, the theoretical chemical composition is Ba 1.97 Eu 0.03 Hf 2.6 Si 2.6 Al 4.4 O 19 materials.

[0057] Reference matrix chemical formula: Ba2Hf2Si5Al2O 19 , considering that Si and Al occupy the same crystallographic position (see Figure 5), the material obtained in comparative example 2 obviously has a high concentration (30%) of Hf interstitial defects (although Eu replaces Ba, the charge number is the same and the radius is close, so the defect effect is not obvious). Therefore, in theory, the luminescence performance of the material obtained in comparative example 2 should be poor. This is indeed the case. The luminescence performance of the corresponding material in comparative example 2 was analyzed using a fluorescence spectrometer. The results show that the main peak of the emission spectrum of the material obtained in comparative example 2 is located at 511 nm, which is cyan light, and the half-width of the emission spectrum is 82nm. Obviously, the performance of the emission spectrum of the material obtained in comparative example 2 is similar to that of comparative example 1. The quantum efficiency of the material corresponding to comparative example 2 was tested using a quantum efficiency tester. The results show that the quantum efficiency of the material obtained in comparative example 2 is only 16.5%, which is an extremely low value. See Table 1 for specific data. Obviously, due to the artificial creation of the interstitial defects of Hf, the luminescence performance (quantum efficiency) of the material obtained in comparative example 2 is significantly lower than that of comparative example 1.

[0058] That is, Comparative Example 2 is a cyan luminescent material with poor performance.

[0059] Comparative Example 3

[0060] The raw materials are BaCO3, Eu2O3, HfO2, SiO2 and Al2O3. The molar ratio of Ba, Eu, Hf, Si and Al in BaCO3, Eu2O3, HfO2, SiO2 and Al2O3 is 1.97:0.03:2.05:4.8:2.2. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1500℃ for 6h in a high temperature furnace under a 9:1 nitrogen and hydrogen mixed atmosphere. Then, the theoretical chemical composition is Ba 1.97 Eu 0.03 Hf 2.05 Si 4.8 Al 2.2 O 19 materials.

[0061] Reference matrix chemical formula: Ba2Hf2Si5Al2O 19, considering that Si and Al occupy the same crystallographic position, the material obtained in comparative example 3 obviously has a lower concentration (2.5%) of Hf interstitial defects (although Eu replaces Ba, the charge number is the same and the radius is close, so the defect effect is not obvious). Therefore, in theory, the luminescence performance of the material obtained in comparative example 3 should be poor (but better than comparative example 2). This is indeed the case. The luminescence performance of the corresponding material in comparative example 3 was analyzed using a fluorescence spectrometer. The results show that the main peak of the emission spectrum of the material obtained in comparative example 3 is located at 510 nm, which is cyan light, and the half-height width of the emission spectrum is 80 nm. Obviously, the performance of the emission spectrum of the material obtained in comparative example 3 is similar to that of comparative examples 1 and 2. The quantum efficiency of the material corresponding to comparative example 3 was tested using a quantum efficiency tester. The results show that the quantum efficiency of the material obtained in comparative example 3 is 53.4%, which is an ordinary value, but significantly improved compared with comparative example 2. See Table 1 for specific data. Obviously, due to the artificial creation of Hf gaps (although the defect concentration is very low), the luminescence performance (quantum efficiency) of the material obtained in comparative example 3 has decreased to a certain extent compared with comparative example 1.

[0062] That is, Comparative Example 3 is a cyan luminescent material with ordinary performance.

[0063] Comparative Example 4

[0064] The raw materials are BaCO3, Eu2O3, HfO2, SiO2 and Al2O3. The molar ratio of Ba, Eu, Hf, Si and Al in BaCO3, Eu2O3, HfO2, SiO2 and Al2O3 is 1.97:0.03:2:4.775:2.3. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1500℃ for 6h in a high temperature furnace under a 9:1 nitrogen and hydrogen mixed atmosphere. Then, the theoretical chemical composition is Ba 1.97 Eu 0.03 Hf2Si 4.775 Al 2.3 O 19 materials.

[0065] Reference matrix chemical formula: Ba2Hf2Si5Al2O 19 Compared with Comparative Examples 2 and 3, there is no Hf interstitial defect in Comparative Example 4. However, although Si and Al occupy the same crystallographic position, the different ratios of Si and Al will inevitably affect the optical band gap and luminescence performance of the material. This is indeed the case. The luminescence performance of the corresponding material in Comparative Example 4 was analyzed using a fluorescence spectrometer, and the results are as follows: Figure 2As shown. The results show that the main peak of the emission spectrum of the material obtained in Comparative Example 4 is located at 496 nm, which is cyan light, and the half-width of the emission spectrum is 79 nm. Obviously, due to the adjustment of the relative ratio of Si and Al, the performance of the emission spectrum of the material obtained in Comparative Example 4 is significantly different from that of Comparative Example 1. The quantum efficiency of the material corresponding to Comparative Example 4 was tested using a quantum efficiency tester. The results show that the quantum efficiency of the material obtained in Comparative Example 4 is 52.5%. See Table 1 for specific data. Obviously, in the absence of obvious defects, only the ratio of Si and Al is changed, which ultimately leads to a certain degree of decrease in the luminescence performance (quantum efficiency) of the material obtained in Comparative Example 4 compared with Comparative Example 1, and the difference in the emission spectrum is also obvious.

[0066] That is, Comparative Example 4 is a cyan light-emitting material having ordinary properties.

[0067] Comparative Example 5

[0068] The raw materials are BaCO3, Eu2O3, HfO2, SiO2 and Al2O3. The molar ratio of Ba, Eu, Hf, Si and Al in BaCO3, Eu2O3, HfO2, SiO2 and Al2O3 is 1.97:0.03:1.775:5:2.3. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1500℃ for 6h in a high temperature furnace under a 9:1 nitrogen and hydrogen mixed atmosphere. Then, the theoretical chemical composition is Ba 1.97 Eu 0.03 Hf 1.775 Si5Al 2.3 O 19 materials.

[0069] Reference matrix chemical formula: Ba2Hf2Si5Al2O 19 , Comparative Example 5 increases the vacancy defects of Hf and increases the Al interstitial defects. Therefore, in theory, the luminescence performance of the material prepared in Comparative Example 5 should be poor. This is indeed the case. The luminescence performance of the corresponding material in Comparative Example 5 was analyzed using a fluorescence spectrometer. The results show that the main peak of the emission spectrum of the material obtained in Comparative Example 5 is located at 493 nm, which is cyan light, and the half-width of the emission spectrum is 78 nm. Obviously, the performance of the emission spectrum of the material obtained in Comparative Example 5 is similar to that of Comparative Example 4. The quantum efficiency of the material corresponding to Comparative Example 5 was tested using a quantum efficiency tester. The results show that the quantum efficiency of the material obtained in Comparative Example 5 is only 11.9%, which is an extremely low value. See Table 1 for specific data. Obviously, due to the artificial creation of Hf vacancy defects and the increase of Al interstitial defects, the luminescence performance (quantum efficiency) of the material obtained in Comparative Example 5 is significantly lower than that in Comparative Example 4.

[0070] That is, Comparative Example 5 is a cyan light-emitting material with poor performance.

[0071] Comparative Example 6

[0072] The raw materials are BaCO3, Eu2O3, HfO2, SiO2 and Al2O3. The molar ratio of Ba, Eu, Hf, Si and Al in BaCO3, Eu2O3, HfO2, SiO2 and Al2O3 is 1.97:0.03:2.3:4.7:2. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1500℃ for 6h in a high temperature furnace under a 9:1 nitrogen and hydrogen mixed atmosphere. Then, the theoretical chemical composition is Ba 1.97 Eu 0.03 Hf 2.3 Si 4.7 Al2O 19 materials.

[0073] Reference matrix chemical formula: Ba2Hf2Si5Al2O 19 , Comparative Example 6 increases the gap defects of Hf and increases the vacancy defects of Si. Therefore, in theory, the luminescence performance of the material obtained in Comparative Example 6 should be poor. This is indeed the case. The luminescence performance of the corresponding material in Comparative Example 6 was analyzed using a fluorescence spectrometer. The results show that the main peak of the emission spectrum of the material obtained in Comparative Example 6 is located at 505 nm, which is cyan light, and the half-width of the emission spectrum is 88 nm. Obviously, the performance of the emission spectrum of the material obtained in Comparative Example 6 is similar to that of Comparative Example 1. The quantum efficiency of the material corresponding to Comparative Example 6 was tested using a quantum efficiency tester. The results show that the quantum efficiency of the material obtained in Comparative Example 6 is only 33.7%, which is an extremely low value. See Table 1 for specific data. Obviously, due to the artificial creation of the gap defects of Hf and the increase of the vacancy defects of Si, the luminescence performance (quantum efficiency) of the material obtained in Comparative Example 6 is significantly lower than that in Comparative Example 1.

[0074] That is, Comparative Example 6 is a cyan luminescent material with poor performance.

[0075] Embodiments 1 to 5

[0076] The raw materials are BaCO3, Eu2O3, HfO2, SiO2 and Al2O3, and the molar ratios of Ba, Eu, Hf, Si and Al in BaCO3, Eu2O3, HfO2, SiO2 and Al2O3 are 1.995:0.005:2.1:4.6:2.4 (Example 1), 1.995:0.005:2.2:4.2:2.8 (Example 2), 1.995:0. 005:2.3:3.8:3.2 (Example 3), 1.995:0.005:2.4:3.4:3.6 (Example 4), 1.995:0.005:2.5:3:4 (Example 5). After grinding and mixing the above raw materials, they were respectively put into crucibles, sintered at 1500°C for 6h in a high temperature furnace under a 9:1 nitrogen and hydrogen mixed atmosphere, and cooled to room temperature with the furnace to obtain materials with the following theoretical chemical composition:

[0077] Ba 1.995 Eu 0.005 Hf 2.1 Si 4.6 Al 2.4 O 19 (Example 1)

[0078] Ba 1.995 Eu 0.005 Hf 2.2 Si 4.2 Al 2.8 O 19 (Example 2)

[0079] Ba 1.995 Eu 0.005 Hf 2.3 Si 3.8 Al 3.2 O 19 (Example 3)

[0080] Ba 1.995 Eu 0.005 Hf 2.4 Si 3.4 Al 3.6 O 19 (Example 4)

[0081] Ba 1.995 Eu 0.005 Hf 2.5 Si3Al4O 19 (Example 5)

[0082] Reference matrix chemical formula: Ba2Hf2Si5Al2O 19, Example 1 increases the interstitial defect of Hf and adjusts the ratio of Si to Al (although Si and Al occupy the same crystallographic position, the different ratios of Si and Al will inevitably affect the optical band gap and luminescence performance of the material). Referring to Comparative Examples 2 to 4, theoretically, the luminescence performance of the material obtained in Example 1 should be poor, but the actual situation is just the opposite. The corresponding phosphor in Example 1 is analyzed using a fluorescence spectrometer to obtain its excitation and emission spectra, as shown in FIG. Figure 3 As shown. The material can absorb ultraviolet to violet light. Under 400 nm violet light excitation, the main peak of the emission spectrum is located at 459 nm, and the half-height width of the emission spectrum is 70 nm. The quantum efficiency of the material was tested using a quantum efficiency tester, and its value was 70.3%, as shown in Table 1. The quantum efficiency value is extremely high, indicating that the material has extremely high packaging practical value. The structure of the material obtained in Example 1 was analyzed by X-ray diffraction using an X-ray diffractometer, and its diffraction spectrum is as shown Figure 4 As shown. By searching and comparing the powder structure database, its diffraction data is completely different from the diffraction patterns of currently known fluorescent materials, which shows that the material obtained in Example 1 is a fluorescent material with a completely new structure. By single crystal diffraction analysis, combined with the data of powder structure refinement, it is shown that the material (matrix, Ba2Hf2Si5Al2O 19 ) belongs to the hexagonal crystal system, and the space group is P63 / m. Figure 5 A diagram of the crystal structure of the material (matrix) is given.

[0083] In Examples 2 to 5, under the excitation of 400 nm violet light, the main peaks of the emission spectra are located at 457 nm (Example 2), 457 nm (Example 3), 456 nm (Example 4) and 455 nm (Example 5), the half-height widths of the emission spectra are 70 nm (Example 2), 71 nm (Example 3), 72 nm (Example 4) and 73 nm (Example 5), and the quantum efficiencies are 76.1% (Example 2), 77.7% (Example 3), 79.8% (Example 4) and 80.8% (Example 5), as shown in Table 1. Similar to Example 1, the luminescent properties of the materials obtained in Examples 2 to 5 are also excellent. Figure 6 A graph showing the changes in the luminescent properties of the materials obtained in implementations 1 to 5 is given.

[0084] It can be seen that the material obtained in Examples 1 to 5 is a high-efficiency narrow-band blue fluorescent material. Under the excitation of 400 nm violet light, the main peak of the emission spectrum of the high-efficiency narrow-band blue fluorescent material is located at 455-475 nm, the half-width is in the range of 70-80 nm, and the quantum efficiency is greater than 70%, so that the fluorescent material can be applied to white light LED devices.

[0085] Embodiments 6 to 10

[0086] The raw materials are BaCO3, Eu2O3, HfO2, SiO2 and Al2O3, and the molar ratio of Ba, Eu, Hf, Si and Al in BaCO3, Eu2O3, HfO2, SiO2 and Al2O3 is 1.99:0.01:2.1:4.6:2.4 (Example 6), 1.99:0.01:2.2:4.2:2.8 (Example 7), 1.99:0.01:2.3:3.8:3.2 (Example 8), 1.99:0.01:2.4:3.4:3.6 (Example 9), 1.99:0.01:2.5:3:4 (Example 10). After grinding and mixing the above raw materials, they are respectively loaded into crucibles, sintered at 1500°C for 6 hours in a high-temperature furnace under a 9:1 nitrogen and hydrogen mixed atmosphere, and cooled to room temperature with the furnace to obtain a material with the following theoretical chemical composition:

[0087] Ba 1.99 Eu 0.01 Hf 2.1 Si 4.6 Al 2.4 O 19 (Example 6)

[0088] Ba 1.99 Eu 0.01 Hf 2.2 Si 4.2 Al 2.8 O 19 (Example 7)

[0089] Ba 1.99 Eu 0.01 Hf 2.3 Si 3.8 Al 3.2 O 19 (Example 8)

[0090] Ba 1.99 Eu 0.01 Hf 2.4 Si 3.4 Al 3.6 O 19 (Example 9)

[0091] Ba 1.99 Eu 0.01 Hf 2.5 Si3Al4O 19 (Example 10)

[0092] Reference matrix chemical formula: Ba2Hf2Si5Al2O 19, implementations 6 to 10 increase the gap defects of Hf, and adjust the ratio of Si and Al at the same time (although Si and Al occupy the same crystallographic position, the ratio of Si and Al is different, which will inevitably affect the optical band gap and luminescence performance of the material). Referring to comparative examples 2 to 4, theoretically, the luminescence performance of the materials obtained in embodiments 6 to 10 should be poor, but the actual situation is just the opposite. The corresponding phosphors in embodiments 6 to 10 were analyzed using a fluorescence spectrometer. The results show that the corresponding materials in embodiments 6 to 10 can absorb ultraviolet to violet light. Under 400 nm violet light excitation, the main peaks of the emission spectrum are located at 461 nm (Example 6), 460 nm (Example 7), 459 nm (Example 8), 458 nm (Example 9) and 458 nm (Example 10), and the half-height width of the emission spectrum is 73 nm (Example 6), 74 nm (Example 7), 72 nm (Example 8), 73 nm (Example 9) and 74 nm (Example 10). The quantum efficiency of Examples 6 to 10 was tested using a quantum efficiency tester, and the values ​​were 75.9% (Example 6), 79.2% (Example 7), 80.1% (Example 8), 82.9% (Example 9) and 83.1% (Example 10), as shown in Table 1. The quantum efficiency values ​​are extremely high, indicating that the material has extremely high packaging practical value. The structures of the materials obtained in Examples 6 to 10 were analyzed by X-ray diffraction using an X-ray diffractometer, and the results were basically the same as those in Example 1. Figure 7 A graph showing the changes in the luminescence properties of the materials obtained in implementations 6 to 10 is given.

[0093] It can be seen that the material obtained in Examples 6 to 10 is a high-efficiency narrow-band blue fluorescent material. Under the excitation of 400 nm violet light, the main peak of the emission spectrum of the high-efficiency narrow-band blue fluorescent material is located at 455 to 475 nm, the half-width is in the range of 70 to 80 nm, and the quantum efficiency is greater than 70%, so that the fluorescent material can be applied to white light LED devices.

[0094] Examples 11 to 15

[0095] The raw materials are BaCO3, Eu2O3, HfO2, SiO2 and Al2O3, and the molar ratio of Ba, Eu, Hf, Si and Al in BaCO3, Eu2O3, HfO2, SiO2 and Al2O3 is 1.98:0.02:2.1:4.6:2.4 (Example 11), 1.98:0.02:2.2:4.2:2.8 (Example 12), 1.98:0.02:2.3:3.8:3.2 (Example 13), 1.98:0.02:2.4:3.4:3.6 (Example 14), 1.98:0.02:2.5:3:4 (Example 15). After grinding and mixing the above raw materials, they are respectively loaded into crucibles, sintered at 1500°C for 6 hours in a high temperature furnace under a 9:1 nitrogen and hydrogen mixed atmosphere, and cooled to room temperature with the furnace to obtain a material with the following theoretical chemical composition:

[0096] Ba 1.98 Eu 0.02 Hf 2.1 Si 4.6 Al 2.4 O 19 (Example 11)

[0097] Ba 1.98 Eu 0.02 Hf 2.2 Si 4.2 Al 2.8 O 19 (Example 12)

[0098] Ba 1.98 Eu 0.02 Hf 2.3 Si 3.8 Al 3.2 O 19 (Example 13)

[0099] Ba 1.98 Eu 0.02 Hf 2.4 Si 3.4 Al 3.6 O 19 (Example 14)

[0100] Ba 1.98 Eu 0.02 Hf 2.5 Si3Al4O 19 (Example 15)

[0101] Reference matrix chemical formula: Ba2Hf2Si5Al2O 19, implementations 11 to 15 increase the gap defects of Hf, and adjust the ratio of Si and Al at the same time (although Si and Al occupy the same crystallographic position, the ratio of Si and Al is different, which will inevitably affect the optical band gap and luminescence performance of the material). Referring to comparative examples 2 to 4, theoretically, the luminescence performance of the materials obtained in embodiments 11 to 15 should be poor, but the actual situation is just the opposite. The corresponding phosphors in embodiments 11 to 15 were analyzed using a fluorescence spectrometer. The results show that the corresponding materials in embodiments 11 to 15 can absorb ultraviolet to violet light. Under 400 nm violet light excitation, the main peaks of the emission spectrum are located at 467 nm (Example 11), 462 nm (Example 12), 465 nm (Example 13), 464 nm (Example 14) and 460 nm (Example 15), and the half-height width of the emission spectrum is 75 nm (Example 11), 77 nm (Example 12), 76 nm (Example 13), 73 nm (Example 14) and 73 nm (Example 15). The quantum efficiency of Examples 11 to 15 was tested using a quantum efficiency tester, and the values ​​were 76.4% (Example 11), 78.9% (Example 12), 79.6% (Example 13), 80.4% (Example 14) and 88.2% (Example 15), as shown in Table 1. The quantum efficiency value is extremely high, indicating that the material has extremely high packaging practical value. The structure of the materials obtained in Examples 11 to 15 was analyzed by X-ray diffraction using an X-ray diffractometer, and the results were basically the same as those in Example 1. Figure 8 A graph showing the changes in the luminescence properties of the materials obtained in implementations 11 to 15 is given.

[0102] It can be seen that the material obtained in Examples 11 to 15 is a high-efficiency narrow-band blue fluorescent material. Under the excitation of 400 nm violet light, the main peak of the emission spectrum of the high-efficiency narrow-band blue fluorescent material is located at 455 to 475 nm, the half-width is in the range of 70 to 80 nm, and the quantum efficiency is greater than 70%, so that the fluorescent material can be applied to white light LED devices.

[0103] Embodiments 16 to 20

[0104] The raw materials are BaCO3, Eu2O3, HfO2, SiO2 and Al2O3, and the molar ratios of Ba, Eu, Hf, Si and Al in BaCO3, Eu2O3, HfO2, SiO2 and Al2O3 are 1.97:0.03:2.1:4.6:2.4 (Example 16), 1.97:0.03:2.2:4.2:2.8 (Example 17), 1.97:0.03:2.3:3.8:3.2 (Example 18), 1.97:0.03:2.4:3.4:3.6 (Example 19), and 1.97:0.03:2.5:3:4 (Example 20). After grinding and mixing the above raw materials, they are respectively loaded into crucibles, sintered at 1500°C for 6 hours in a high-temperature furnace under a 9:1 nitrogen and hydrogen mixed atmosphere, and cooled to room temperature with the furnace to obtain a material with the following theoretical chemical composition:

[0105] Ba 1.97 Eu 0.03 Hf 2.1 Si 4.6 Al 2.4 O 19 (Example 16)

[0106] Ba 1.97 Eu 0.03 Hf 2.2 Si 4.2 Al 2.8 O 19 (Example 17)

[0107] Ba 1.97 Eu 0.03 Hf 2.3 Si 3.8 Al 3.2 O 19 (Example 18)

[0108] Ba 1.97 Eu 0.03 Hf 2.4 Si 3.4 Al 3.6 O 19 (Example 19)

[0109] Ba 1.97 Eu 0.03 Hf 2.5 Si3Al4O 19 (Example 20)

[0110] Reference matrix chemical formula: Ba2Hf2Si5Al2O 19, implementations 16 to 20 increase the gap defects of Hf, and adjust the ratio of Si and Al at the same time (although Si and Al occupy the same crystallographic position, the ratio of Si and Al is different, which will inevitably affect the optical band gap and luminescence performance of the material). Referring to comparative examples 2 to 4, theoretically, the luminescence performance of the materials obtained in embodiments 16 to 20 should be poor, but the actual situation is just the opposite. The corresponding phosphors in embodiments 16 to 20 were analyzed using a fluorescence spectrometer. The results show that the corresponding materials in embodiments 16 to 20 can absorb ultraviolet to violet light. Under 400 nm violet light excitation, the main peaks of the emission spectrum are located at 470 nm (Example 16), 470 nm (Example 17), 465 nm (Example 18), 463 nm (Example 19) and 460 nm (Example 20), and the half-height width of the emission spectrum is 77 nm (Example 16), 80 nm (Example 17), 78 nm (Example 18), 76 nm (Example 19) and 77 nm (Example 20). The quantum efficiency of Examples 16 to 20 was tested using a quantum efficiency tester, and the values ​​were 85.5% (Example 16), 89.1% (Example 17), 93.2% (Example 18), 92.3% (Example 19) and 90.3% (Example 20), as shown in Table 1. The quantum efficiency value is extremely high, indicating that the material has extremely high packaging practical value. The structure of the materials obtained in Examples 16 to 20 was analyzed by X-ray diffraction using an X-ray diffractometer, and the results were basically the same as those in Example 1. Fig. 9 A graph showing the changes in the luminescence properties of the materials obtained in implementations 16 to 20 is given.

[0111] It can be seen that the material obtained in Examples 16 to 20 is a high-efficiency narrow-band blue fluorescent material. Under the excitation of 400 nm violet light, the main peak of the emission spectrum of the high-efficiency narrow-band blue fluorescent material is located at 455 to 475 nm, the half-width is in the range of 70 to 80 nm, and the quantum efficiency is greater than 70%, so that the fluorescent material can be applied to white light LED devices.

[0112] Examples 21 to 25

[0113] The raw materials are BaCO3, Eu2O3, HfO2, SiO2 and Al2O3, and the molar ratios of Ba, Eu, Hf, Si and Al in BaCO3, Eu2O3, HfO2, SiO2 and Al2O3 are 1.96:0.04:2.1:4.6:2.4 (Example 21), 1.96:0.04:2.2:4.2:2.8 (Example 22), 1.96:0.04:2.3:3.8:3.2 (Example 23), 1.96:0.04:2.4:3.4:3.6 (Example 24), and 1.96:0.04:2.5:3:4 (Example 25). After grinding and mixing the above raw materials, they are respectively loaded into crucibles, sintered at 1500°C for 6 hours in a high-temperature furnace under a 9:1 nitrogen and hydrogen mixed atmosphere, and cooled to room temperature with the furnace to obtain a material with the following theoretical chemical composition:

[0114] Ba 1.96 Eu 0.04 Hf 2.1 Si 4.6 Al 2.4 O 19 (Example 21)

[0115] Ba 1.96 Eu 0.04 Hf 2.2 Si 4.2 Al 2.8 O 19 (Example 22)

[0116] Ba 1.96 Eu 0.04 Hf 2.3 Si 3.8 Al 3.2 O 19 (Example 23)

[0117] Ba 1.96 Eu 0.04 Hf 2.4 Si 3.4 Al 3.6 O 19 (Example 24)

[0118] Ba 1.96 Eu 0.04 Hf 2.5 Si3Al4O 19 (Example 25)

[0119] Reference matrix chemical formula: Ba2Hf2Si5Al2O 19, implementations 21 to 25 increase the gap defects of Hf, and adjust the ratio of Si and Al at the same time (although Si and Al occupy the same crystallographic position, the ratio of Si and Al is different, which will inevitably affect the optical band gap and luminescence performance of the material). Referring to comparative examples 2 to 4, theoretically, the luminescence performance of the materials obtained in embodiments 21 to 25 should be poor, but the actual situation is just the opposite. The corresponding phosphors in embodiments 21 to 25 were analyzed using a fluorescence spectrometer. The results show that the corresponding materials in embodiments 21 to 25 can absorb ultraviolet to violet light. Under 400 nm violet light excitation, the main peaks of the emission spectrum are located at 472 nm (Example 21), 471 nm (Example 22), 470 nm (Example 23), 469 nm (Example 24) and 468 nm (Example 25), and the half-height width of the emission spectrum is 78 nm (Example 21), 79 nm (Example 22), 80 nm (Example 23), 78 nm (Example 24) and 75 nm (Example 25). The quantum efficiency of Examples 21 to 25 was tested using a quantum efficiency tester, and the values ​​were 91.6% (Example 21), 91.5% (Example 22), 90.8% (Example 23), 89.4% (Example 24) and 88.5% (Example 25), as shown in Table 1. The quantum efficiency value is extremely high, indicating that the material has extremely high packaging practical value. The structure of the materials obtained in Examples 21 to 25 was analyzed by X-ray diffraction using an X-ray diffractometer, and the results were basically the same as those in Example 1. Fig.10 A graph showing the changes in the luminescent properties of the materials obtained in Examples 21 to 25 is given.

[0120] It can be seen that the material obtained in Examples 21 to 25 is a high-efficiency narrow-band blue fluorescent material. Under the excitation of 400 nm violet light, the main peak of the emission spectrum of the high-efficiency narrow-band blue fluorescent material is located at 455 to 475 nm, the half-width is in the range of 70 to 80 nm, and the quantum efficiency is greater than 70%, so that the fluorescent material can be applied to white light LED devices.

[0121] Embodiments 26 to 30

[0122] The raw materials are BaCO3, Eu2O3, HfO2, SiO2 and Al2O3, and the molar ratios of Ba, Eu, Hf, Si and Al in BaCO3, Eu2O3, HfO2, SiO2 and Al2O3 are 1.95:0.05:2.1:4.6:2.4 (Example 26), 1.95:0.05:2.2:4.2:2.8 (Example 27), 1.95:0.05:2.3:3.8:3.2 (Example 28), 1.95:0.05:2.4:3.4:3.6 (Example 29), and 1.95:0.05:2.5:3:4 (Example 30). After grinding and mixing the above raw materials, they are respectively loaded into crucibles, sintered at 1500°C for 6 hours in a high-temperature furnace under a 9:1 nitrogen and hydrogen mixed atmosphere, and cooled to room temperature with the furnace to obtain a material with the following theoretical chemical composition:

[0123] Ba 1.95 Eu 0.05 Hf 2.1 Si 4.6 Al 2.4 O 19 (Example 26)

[0124] Ba 1.95 Eu 0.05 Hf 2.2 Si 4.2 Al 2.8 O 19 (Example 27)

[0125] Ba 1.95 Eu 0.05 Hf 2.3 Si 3.8 Al 3.2 O 19 (Example 28)

[0126] Ba 1.95 Eu 0.05 Hf 2.4 Si 3.4 Al 3.6 O 19 (Example 29)

[0127] Ba 1.95 Eu 0.05 Hf 2.5 Si3Al4O 19 (Example 30)

[0128] Reference matrix chemical formula: Ba2Hf2Si5Al2O 19, implementations 26 to 30 increase the gap defects of Hf, and adjust the ratio of Si and Al at the same time (although Si and Al occupy the same crystallographic position, the ratio of Si and Al is different, which will inevitably affect the optical band gap and luminescence performance of the material). Referring to comparative examples 2 to 4, theoretically, the luminescence performance of the materials obtained in embodiments 26 to 30 should be poor, but the actual situation is just the opposite. The corresponding phosphors in embodiments 26 to 30 were analyzed using a fluorescence spectrometer. The results show that the corresponding materials in embodiments 26 to 30 can absorb ultraviolet to violet light. Under 400 nm violet light excitation, the main peaks of the emission spectrum are located at 475 nm (Example 26), 473 nm (Example 27), 475 nm (Example 28), 474 nm (Example 29) and 469 nm (Example 30), and the half-height width of the emission spectrum is 80 nm (Example 26), 78 nm (Example 27), 80 nm (Example 28), 77 nm (Example 29) and 76 nm (Example 30). The quantum efficiency of Examples 26 to 30 was tested using a quantum efficiency tester, and the values ​​were 87.4% (Example 26), 85.6% (Example 27), 86.3% (Example 28), 82.9% (Example 29) and 82.7% (Example 30), as shown in Table 1. The quantum efficiency value is extremely high, indicating that the material has extremely high packaging practical value. The structure of the material obtained in Examples 26 to 30 was analyzed by X-ray diffraction using an X-ray diffractometer, and the results were basically the same as those in Example 1. Fig.11 A graph showing the changes in the luminescence properties of the materials obtained in implementations 26 to 30 is given.

[0129] It can be seen that the material obtained in Examples 26 to 30 is a high-efficiency narrow-band blue fluorescent material. Under the excitation of 400 nm violet light, the main peak of the emission spectrum of the high-efficiency narrow-band blue fluorescent material is located at 455 to 475 nm, the half-width is in the range of 70 to 80 nm, and the quantum efficiency is greater than 70%, so that the fluorescent material can be applied to white light LED devices.

[0130] Table 1 Luminescent properties of materials corresponding to comparative examples and examples

[0131]

[0132]

[0133] Embodiment 31

[0134] The chemical formula of the synthesis of Example 18 is Ba 1.97 Eu 0.03 Hf 2.3 Si 3.8 Al 3.2 O 19 Blue fluorescent material, Lu3Al5O12 :Ce green fluorescent material and Sr 0.9 Ca 0.1 AlSiN3:Eu red fluorescent material is mixed evenly with epoxy resin in a mass ratio of 1:0.77:0.39:5.2, and the mixture is coated on a purple LED with a main peak of emission spectrum at 409 nm, encapsulated, and then cured at 150°C for 2h to obtain a white light LED device with a color rendering index of 90.2. The spectrum of the device is shown in Fig.12 shown.

[0135] The above embodiments are only used to illustrate the implementation methods of the present invention and to explain the technical features of the present invention, and are not used to limit the protection scope of the present invention. Any changes or equivalent arrangements that can be easily completed by a person familiar with this technology belong to the scope claimed by the present invention, and the scope of protection of the present invention shall be subject to the claims.

Claims

1. A high-efficiency narrow-band blue fluorescent material, characterized by: The chemical formula of the high-efficiency narrow-band blue fluorescent material is Ba 2-x Eu x Hf 2+y Si 5-4y Al 2+4y O 19 , where 0<x≤0.05, 0.1≤y≤0.5; under the excitation of 400 nm violet light, the main peak of the emission spectrum is located at 455~475 nm, the half-width is 70~80 nm, and the quantum efficiency is >70%.

2. A high-efficiency narrow-band blue fluorescent material as claimed in claim 1, characterized in that: The x is 0.03 and the y is 0.

3.

3. The method for preparing a high-efficiency narrow-band blue fluorescent material according to any one of claims 1 to 2, characterized in that: A Ba precursor, a Eu precursor, a Hf precursor, a Si precursor and an Al precursor are mixed and subjected to a high-temperature solid-phase reaction in a reducing atmosphere to obtain the high-efficiency narrow-band blue fluorescent material.

4. The method for preparing a high-efficiency narrow-band blue fluorescent material according to claim 3, characterized in that: The molar ratio of Ba, Eu, Hf, Si and Al in the Ba precursor, Eu precursor, Hf precursor, Si precursor and Al precursor is (2-x):x:(2+y): (5-4y):(2+4y), wherein 0<x≤0.05, 0.1≤y≤0.

5.

5. The method for preparing a high-efficiency narrow-band blue fluorescent material according to claim 3, characterized in that: The Ba precursor is selected from one or more of Ba carbonate, Ba oxide, Ba oxalate and Ba nitrate; the Eu precursor is selected from one or more of Eu carbonate, Eu oxide, Eu oxalate and Eu nitrate.

6. The method for preparing a high-efficiency narrow-band blue fluorescent material according to claim 3, characterized in that: The Hf precursor is selected from HfO2; the Si precursor is selected from SiO2; the Al precursor is selected from one or more of Al carbonate, Al oxide, Al oxalate and Al nitrate.

7. The method for preparing a high-efficiency narrow-band blue fluorescent material according to claim 3, characterized in that: The temperature of the high temperature solid phase reaction is 1400-1600° C., and the time of the high temperature solid phase reaction is 4-10 hours.

8. Use of a high-efficiency narrow-band blue fluorescent material according to any one of claims 1 to 2 or a high-efficiency narrow-band blue fluorescent material obtained by the preparation method according to any one of claims 3 to 7, characterized in that: Used to prepare white light LED devices.

9. A white light LED device, characterized in that: The invention comprises a high-efficiency narrow-band blue fluorescent material as described in any one of claims 1 to 2 or a high-efficiency narrow-band blue fluorescent material obtained by the preparation method as described in any one of claims 3 to 7.

10. A white light LED device as claimed in claim 9, characterized in that: It also includes a purple LED chip that can emit a peak wavelength between 380 and 425 nm.

Citation Information

Patent Citations

  • Europium-activated silicate blue-light fluorescent powder and preparation method thereof

    CN110951489A

  • Cyan oxide fluorescent material capable of being excited by purple light and preparation method

    CN117568033A